Pengaruh Arus Las Smaw Kampuh V Metode 1gplat Datar Alur Segitigaterhadap Kekuatan Las Pada Material AISI 1016 - Isra, Adi; N, Nazarudin; W, Weriono (Rekayasa Material, Manufaktur dan Energi, 2022)
The nature of electrode with the base metal is as important as the welding speed and design of joint. One of the metal joining systems is the SMAW (shielded Metal Arc Welding) welding system with wrapped electrodes. Generally, for welding high strength steels a higher heat input is used in the SMAW process compared to other processes. The influence of heat input and welding speed affects the characteristics of the material, microstructural properties and mechanical properties of the weld. The type of electrode used is current according to the material to be welded, in this case the author uses AWS E-7016 welding wire with D32 mm and AISI 1016 material with a thickness of 12 mm using V connection. The welding process occurs because of the resistance of an electric current flowing between the electrode and the welding material which causes heat to reach 30000C, thus making the electrode and the material to be welded melt. Welding currents of 100 A and 120 A have tensile strength, ultimate strength and elongation above 20% which is the result of the same good strength as the parent metal.The purpose of this study was to obtain the tensile strength and bending strength of the welded joint with V seam welding and to compare the results of the tensile strength and bending strength with the effect of high current variations on the electrode during welding.The results of the buckling test for a current of 80 a showed a fracture in the WM/HAZ, fracture occurred in the welding area, while for a current of 100 A, fine cracks were obtained in the WM/HAZ in the weld area and a current of 120 A obtained a Void: 0.8 with better welding results.